Effect of destabilized reactions using lithium amide (LiNH2) and doping using titanium based catalyst on the desorption characteristics of lithium aluminum hydride (LiAlH4) - Paravasthu, Siddharth, author; James, Susan P., advisor; Sampath, Walajabad S., committee member; Wu, Mingzhong, committee member (Colorado State University. Libraries, 2012)
In the past few decades there has been a tremendous increase in hydrogen storage research. Numerous materials and material systems have been studied as potential candidates for hydrogen storage, but unfortunately none of those materials demonstrate enough hydrogen releasing capacity under suitable temperature range to be used for hydrogen storage. Research promises to unlock the potential of these materials and ultimately lead to the commercialization of this technology. LiAlH4 is one of those materials that have been exclusively studied as a candidate for hydrogen storage due to its high theoretical hydrogen storage capacity, and its ability to release hydrogen in more than one step at different temperature ranges. Jun Lu and Zhigang Zak Fang studied the effects of titanium based catalyst (TiCl3.1/3AlCl3) and destabilization reactions using LiNH2 on LiAlH4, but did not demonstrate the effects of ball milling on the system. In the present work we have investigated the effects of ball milling, and the effects of destabilization reaction using LiNH2 on the hydrogen release characteristics of LiAlH4 doped with TiCl3. The current market scenario for fuel cell technology and the possibility and consequences of introducing the current system in the market has been briefly discussed. X-ray powder diffraction, thermo-gravimetric analysis and scanning electron microscopy were employed for the characterization of the samples. Both the compounds LiNH2, and TiCl3 worked in effecting the dehydrogenation kinetics of LiAlH4. The duration of ball milling required to affect the dehydrogenation kinetics of LiAlH4 using TiCl3 was optimized. A hydrogen release of 7.3 wt% was observed from the final system i.e. (LiAlH4/LiNH2 doped with 2% TiCl3) at temperatures below 4000C.